The Effect of Clinical Dental Hygienist's Moral Sensitivity and Psychological Well-Being on Job Engagement - Ye-Seul Han; Young-Im Kim (The Korean Society of Dental Hygiene Science, 2020)
Background: The present study aimed to provide basic data to establish a foundation for efficient operation of the organization by identifying the effects of factors related to moral sensitivity and psychological well-being on job engagement of clinical dental hygienists.Methods: This cross-sectional survey consisted of self-administration questionnaires. After the approval by the Institutional Review Board, a survey was conducted from September 2019 to November 2019, targeting dental hygienists with clinical experience of 1 year or more. A total of 189 questionnaires were analyzed using SPSS 18.0 for Windows. The data were analyzed using average standard deviation, t-test, one-way analysis of variance, Scheffe test, Pearson's correlation analysis, and multiple regression analysis.Results: According to job-related characteristics, higher job engagement was associated with more amount of clinical experience, less turnover intention, higher positions, and occasional job fatigue. Job engagement was improved by increasing moral sensitivity and psychological well-being of clinical dental hygienists. The factors affecting job engagement revealed that along with clinical career, the sub-areas of job engagement, namely turnover intention, moral sensitivity, and psychological well-being had statistically significant influence on job engagement and the explanatory power of the model was approximately 44.8%.Conclusion: Joy of working as a clinical dental hygienist, clinical career, turnover intention, moral sensitivity, and psychological well-being were confirmed as influencing factors that affected job engagement of clinical dental hygienists. It is necessary to establish an effective plan to improve job engagement by increasing moral sensitivity and psychological well-being of clinical dental hygienists.